Fungal Pathogens: Shape-Shifting Invaders. Issue 11 (November 2020) - Min, Kyunghun; Neiman, Aaron M.; Konopka, James B.
Abstract : Fungal infections are on the rise due to new medical procedures that have increased the number of immune compromised patients, antibacterial antibiotics that disrupt the microbiome, and increased use of indwelling medical devices that provide sites for biofilm formation. Key to understanding the mechanisms of pathogenesis is to determine how fungal morphology impacts virulence strategies. For example, small budding cells use very different strategies to disseminate compared with long hyphal filaments. Furthermore, cell morphology must be monitored in the host, as many fungal pathogens change their shape to disseminate into new areas, acquire nutrients, and avoid attack by the immune system. This review describes the shape-shifting alterations in morphogenesis of human fungal pathogens and how they influence virulence strategies. Highlights: Fungal pathogens grow in different shapes that influence their ability to disseminate an infection. For example, small spores (conidia) penetrate deep into the lung, budding cells that are about the size of a red blood cell disseminate in the bloodstream, and long hyphal filaments grow invasively into solid tissues. Some fungi undergo shape shifting in the host to form larger cells, or clusters of cells, that are too big to be eaten (phagocytosed) by leukocytes. Other fungi form small yeasts that have developed strategies for surviving inside the phagosome where they are safe from attack by other immune cells. This also allows them to disseminate throughout the host in a Trojan horse mechanism. Fungal shape shifting can also enhance growth in the host by creating interconnected networks of hyphal filaments (mycelia) that promote sharing of nutrients.